1995
DOI: 10.1161/01.cir.91.3.776
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Plaque Disruption and Arterial Thrombosis in an Atherosclerotic Rabbit Model

Abstract: A suitable animal model is available for the study of plaque disruption and arterial thrombosis. Hypercholesterolemia and mechanical arterial wall injury seemed to produce plaques vulnerable to triggering of disruption and thrombosis, whereas normal arteries were relatively resistant to triggering. This model provides a method to evaluate agents that might decrease the occurrence of vulnerable plaques or the amount of thrombus formed after triggering. Most important, the model can be used to identify the featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
0
8

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 27 publications
5
97
0
8
Order By: Relevance
“…An animal model of in vivo arterial thrombosis without acute manipulation of the vessel wall can be useful to study the process of thrombus formation and related acute ischemic events. The model presented here produced rates of thrombosis similar to those of the study of Abela et al (3). The rabbit model of balloon desendothelization produced a large number of thrombi with minimal surgery-related complications.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…An animal model of in vivo arterial thrombosis without acute manipulation of the vessel wall can be useful to study the process of thrombus formation and related acute ischemic events. The model presented here produced rates of thrombosis similar to those of the study of Abela et al (3). The rabbit model of balloon desendothelization produced a large number of thrombi with minimal surgery-related complications.…”
supporting
confidence: 79%
“…Using this protocol, the rabbit aorta showed disrupted atherosclerotic plaques with overlying thrombi. Recently, Abela et al (3) reproduced this model and were able to increase the in vivo proportion of thrombosis after 8 months by adding arterial balloon desendothelization to the high-cholesterol diet intervention. In the present study, we tested the hypothesis that aortic desendothelization performed only 4 months before the triggering protocol without a high cholesterol diet is an effective and less expensive way of pro-ducing arterial atherosclerosis and thrombosis in the rabbit model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, spontaneous plaque rupture does not occur in these animals, although provocative "triggering" stimuli may provoke arterial thrombosis in cholesterol-fed rabbits. 41 The combination of an initial balloon injury with concomitant hypercholesterolemia was chosen to produce lesions that resemble those in humans more closely than lesions produced by hypercholesterolemia alone. Rabbit lesions produced by injury plus lipid do form a fibrous cap populated by actin-positive smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that age is also a critical factor for the lesions, with 3-to 4.5-yearold rabbits exhibiting fibrotic plaques while young rabbits (4 months) do not (Spagnoli et al, 1991). To induce more advanced lesions, such as a fibrous cap with a high amount of smooth muscle cells in the thoracic and abdominal aorta, a high cholesterol diet must be combined with a single or double balloon injury (Abela et al, 1995;Aikawa et al, 1998;Worthley et al, 2000). Additionally, pharmacological triggering in combination with balloon injury results in the formation of plaques that are similar to those found in human coronary arteries (Johnstone et al, 2001).…”
Section: Rabbitsmentioning
confidence: 99%